The Dynamics of Transnational Religious Movements on the Resilience of the Pancasila Ideology - Sholehoddin; Mohammad Azka Al Azkiya; Ilhamda Fattah Kaloko; Aisyah Chairil (Jurnal Pelita Raya, 2025)
Amid the tide of religious transnationalism that makes faith a cross-border political identity, the resilience of the Pancasila ideology is tested not only by overt threats but primarily by the nation's capacity to maintain national consensus. This study uses a mixed-methods approach with a convergent-integrative design that simultaneously combines non-interactive qualitative and quantitative analysis, recognising that the dynamics of transnational religious movements and the resilience of the Pancasila ideology are ideological, discursive, and structural phenomena that require in-depth analysis and empirical measurement. The results confirm that the dynamics of transnational religious movements interact with the resilience of the Pancasila ideology through three interlocking channels, namely an algorithm-based digital da'wah ecosystem that normalises radicalisation and shifts civic loyalty towards a political ummah, cross-border funding infrastructure that converts philanthropy into an instrument for regulating the social agenda as well as substituting the function of the state, and institutional strategies that engineer official norms through education, local regulations, bureaucracy, social certification, and soft law mechanisms that often escape public scrutiny. This synthesis refines the findings of previous studies that usually stop at violent extremism by showing that the erosion of national consensus more often occurs through discursive normalisation, service dependency, and standardisation of piety that appears pious but gradually shifts constitutional legitimacy.